Arterial hypertension secondary to genetic pheochromocytoma and renal hypoatrophy in pediatric age (Archives of Pediatrics of Uruguay, 2025)
Arterial hypertension (AH) is an increasing trend in pediatrics. Timely diagnosis and treatment can help identify underlying causes and prevent both acute and long-term complications. Pheochromocytomas and paragangliomas are rare causes of AH in children.The objective is to report a case of AH secondary to a genetically determined pheochromocytoma, associated with ipsilateral renal atrophy.We present the case of a 9-year-old asymptomatic school-age girl with severe chronic AH, normal kidney function, and no target organ damage. Ultrasound and angiography revealed a nodule in the right adrenal topography. A DMSA scan showed 12% uptake in the right kidney. Urinary metanephrines and renin levels were markedly elevated. PET confirmed the presence of a pheochromocytoma without dissemination.After a gradual decrease in blood pressure, surgical resection was performed. Histopathological analysis confirmed the diagnosis and its benign nature. Genetic testing identified the pathogenic variant c.72+1G>A in the SDHB gene. Postoperatively, AH persisted, but metanephrine levels normalized. Doppler ultrasound showed hypovascularization in the upper half of the kidney, and DMSA uptake decreased to 9%. A nephrectomy was performed. Blood pressure normalized in the office setting, but ambulatory blood pressure monitoring remained abnormal. Multidisciplinary follow-up is essential for this monorenal patient, who presents with masked AH and remains at risk for tumor recurrence and malignancy.
Keywords: Hypertension; Pheochromocytoma; Child